2021
DOI: 10.3390/dj10010001
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Existing Reflective Practices Used by Undergraduate Dental Students in Paediatric Dentistry

Abstract: Background: Reflection is increasingly significant for dental students and professionals and is a continuing requirement of dental regulatory bodies. There is a paucity of evidence regarding how best to facilitate deep reflection for dental students. This study explored whether the use of clinical logbooks in undergraduate clinical attachments in Paediatric Dentistry was facilitating deep reflection. Methods: This qualitative study used individual interviews for data collection. This was conducted at the Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…A recent literature review highlighted the need for a systematic overhaul of current methods of facilitating reflective practice in dentistry [10]. Furthermore, qualitative research by this team has demonstrated that the use of a written clinical logbook (Figure 1) to engage undergraduate dental students in deep reflection is unhelpful [11]. This study identified several barriers to reflective practice (Table 1) through the lens of the student, rather than educators, to whom these barriers had been invisible, justifying the need for a collaborative approach which involves students in the design and development of reflective practice.…”
Section: Background and Need For Innovationmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent literature review highlighted the need for a systematic overhaul of current methods of facilitating reflective practice in dentistry [10]. Furthermore, qualitative research by this team has demonstrated that the use of a written clinical logbook (Figure 1) to engage undergraduate dental students in deep reflection is unhelpful [11]. This study identified several barriers to reflective practice (Table 1) through the lens of the student, rather than educators, to whom these barriers had been invisible, justifying the need for a collaborative approach which involves students in the design and development of reflective practice.…”
Section: Background and Need For Innovationmentioning
confidence: 99%
“…Students questioned the value of compulsory reflection on every patient contact that they had Online options Flexibility in the method of reflection, including online options and apps were suggested to better engage students in the reflective process Table 1 A summary of the key findings of "It's like two stars and a wish": A qualitative exploration of existing reflective practices used by undergraduate dental students [11].…”
Section: Optional Activitymentioning
confidence: 99%
See 3 more Smart Citations